Novel multiferroic (Pb1 − 3x/2Ndx)(Ti0.98 − yFeyMn0.02)O3 ceramics with coexisting ferroelectricity and ferromagnetism at ambient temperature. (15th November 2016) - Craciun, F.; Cernea, M.; Fruth, V.; Zaharescu, M.; Atkinson, I.; Stanica, N.; Tanase, L.C.; Diamandescu, L.; Iuga, A.; Galassi, C.
Abstract: We report the evolution of structural, dielectric, ferroelectric and ferromagnetic properties in novel (Pb1 − 3x/2 Ndx )(Ti0.98 − y Fey Mn0.02 )O3 perovskite ceramics(x = 0.08, 0 < y < 0.05). We found room-temperature ferroelectric polarization and ferromagnetism for higher amount of iron ions(y ≥ 0.04). The paraelectric-ferroelectric phase transition occurred between 650 and 670 K for 0 ≤ y ≤ 0.05. Ferromagnetic hysteresis was measured at different temperatures on samples with y ≥ 0.04. Detailed structural analysis evidenced the variation of unit cell parameters with y increasing, confirming the substitution of the iron element in the lattice. 57 Fe Mössbauer spectroscopy evidenced that iron ions occupy Ti positions in the perovskite lattice, with the oxidation state Fe 3 + and two coordination types. X-ray photoelectron spectroscopy confirmed the presence of iron only as Fe 3 + and, moreover, evidenced the presence of a substantial amount of Ti 3 + ions in the structure. The presence of both Fe 3 + (spin 5/2) in different coordinations as well as Ti 3 + (spin 1/2) magnetic ions in B-site positions drives the occurrence of magnetic properties from low temperature to above room temperature, through superexchange Fe 3 + -O-Fe 3 +, Fe 3 + -O-Ti 3 + and Ti 3 + -O-Ti 3 + interactions. The finding of coexistent ferroelectric and ferromagnetic properties in these compounds ground the route to facile synthesis of multiferroics by simply doping a classical perovskite ferroelectric material like PbTiO3 with an adequate amount of transition magnetic ions. Graphical abstract: Highlights: Dielectric permittivity enhanced markedly with Fe addition, nearly doubling at transition temperature. The temperature of ferroelectric transition increased with Fe addition from 650 to 670 K. Compositions with more than 3 at.% Fe show ferromagnetic properties at room temperature. Coexistent ferroelectric properties have been found on all compositions.